2018
DOI: 10.1103/physrevd.98.035021
|View full text |Cite
|
Sign up to set email alerts
|

Axion interferometry

Abstract: We propose using interferometry of circularly polarized light as a mechanism by which to test for axion dark matter. These interferometers differ from standard interferometers only by the addition of a few quarter wave plates to preserve the polarization of light upon reflection. We show that using current technology, interferometers can probe new regions of axion parameter space up to a couple orders of magnitude beyond current constraints.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 29 publications
2
94
0
Order By: Relevance
“…[30][31][32][33]. Recent studies [34][35][36] suggested to test this effect with laser interferometry. It should be noted that these works were considering a constant phase shift experienced by photons.…”
Section: Theoretical Calculation Of the Expected Effectmentioning
confidence: 99%
“…[30][31][32][33]. Recent studies [34][35][36] suggested to test this effect with laser interferometry. It should be noted that these works were considering a constant phase shift experienced by photons.…”
Section: Theoretical Calculation Of the Expected Effectmentioning
confidence: 99%
“…We estimated the potential sensitivity of detectors to the axion-photon coupling in a broad mass range 10 −16 eV m 10 −9 eV with the experimental parameters of existing gravitational wave detector projects, such as DECIGO, CE and aLIGO. As a result, we found that their sensitivities can reach beyond the current limit of CAST [5] with a wide axion mass range and can be competitive with other experimental proposals which were recently suggested [25][26][27]. Remarkably, our new scheme for axion-like dark matter search can be performed with a minor modification of the gravitational wave detector and coexist with its observation run for gravitational waves.…”
Section: Sensitivity To the Axion-photon Couplingmentioning
confidence: 62%
“…The dashed lines are projected limits from ALPS-II [12], IAXO [13] and ABRACADABRA broadband configuration with 5 T and 1 m 3 [14]. The expected limits from Axion Interferometry proposal with intra-cavity power of 1 MW [2], the expected integrated limits from ADBC experiment with intra-cavity power of 1 MW [3], and the expected sensitivity of Advanced LIGO with a scheme proposed in Ref. [5] are also shown with dashed lines for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The proposal in Ref. [2] uses linear cavities with quarter-wave plates inside to preserve the polarization of light. The proposal in Ref.…”
Section: Introductionmentioning
confidence: 99%